Input-Output Analysis for Cost Accounting, Planning and Control: A Reply. - Livingstone, J. Leslie (The Accounting Review, 1973)
The article presents the author's response to a commentary on input-output analysis for cost accounting, planning and control. The author relates that the commentary's writer talked of the cost allocation model when referring to the use of a system of linear equations to represent apportionment of costs among interacting departments. The author said that it is not clear to the commentary's writer how the term model can be applied in such case. He explains that it would seem that the linear system itself could be termed a model, independently of the use to which it is put.